INFORMATION TECHNOLOGIES IN THE TRAINING OF HIGHLY QUALIFIED FOOTBALL PLAYERS.: INFORMATION TECHNOLOGIES IN THE TRAINING OF HIGHLY QUALIFIED FOOTBALL PLAYERS. - joraboyev, abdukarim (Физическое воспитание, спорт и здоровье, 2022)
The paper presents an analysis of information technologies used in foreign professional football clubs. The analysis of the application of modern technologies in football teams of Uzbekistan is made. Proposals were made to change the system of training coaches using the latest technologies